Knowledge management, body-shopping and frustrations: search for morality in a postmodernist Era - Dasgupta, Ananda (2003)
Knowledge management hinges upon the presumption that workers within an organizatin possess knowledge that can be converted into concrete business improvements if the information is harvested and disseminated to others to whom it could be of use. True knowledge management must involve capturing the internal knowledge generated by a firm - its best thinking on products, customers, competitors and processes - and sharing it. Insofar as organizations are concerned, postmodernists argue that one view that has been inappropriately privileged is that of the organization rather than the process of organizing. They draw our attention to the link between individual and collective identity. If there is a link between individual identity and how that individual behaves, there may also a link between collective identity and organizational action, for which a study on discourse ethics is essential. After considering the implications of knowledge management and the actual situation and work culture where the knowledge workers are in action, this paper raises and explores the questions wherein lies our individual identity and what its functional relationship with the collective identity is. It has been envisaged in this article that through principles - driven cross-functional teams and innovative organizational mechanisms, sharing and conviction building need to be facilitated in modern organizations phasing our bureaucratic approaches and hierarchical power domination. Flexibility with a focused attitude is a must for organizations to adapt in a changing environment. - Reproduced.
Keywords: Knowledge management